Aleutian Canada goose recovery plan - Aleutian Canada Goose Recovery Team.; U.S. Fish and Wildlife Service. (Anchorage, Alaska : The Team, 1991)
Cover title. Bibliography: p. 38-40. Mode of access: Internet.